Implementasi Pengembangan Sumber Daya Manusia Pada PT. Wijayaperkasa Indah Mojokerto (Jurnal Strategi dan Bisnis, 2022)
The purpose of this study was to analyze the implementation of human resource development applied at PT. Wijayaperkasa Indah Mojokerto. PT. Wijayaperkasa Indah is a manufacturing company engaged in the processing of logs into semi-finished and finished wood materials and is included in the wood building goods industry. Human resource development applied at PT. Wijayaperkasa Indah is through training and promotion. There are obstacles in the implementation of the training in the form of employee indiscipline in participating in the training and the lack of employee awareness of the importance of the training provided so that employees are not enthusiastic in participating in the training so that many employees do not attend even though employees who attend training properly will be rewarded in the form of promotions. Employees are not disciplined in attending training because the training is not in accordance with the need to work more efficiently and effectively according to company standards so that the results of wood products produced by the production division of PT. Wijayaperkasa Indah still has high product damage. This product damage indicates that the work skills in the production division have stagnated so that the company's management develops human resources to improve employee skills through training.